DESAIN MODEL EKOSISTEM RIPARIAN GUNUNG MERAPI BERBASIS ANALISIS KOMODITAS VEGETASI KONSERVASI AIR - Yuslinawari (Jurnal Wana Tropika, 2019)
The study aims to determine the characteristics of the distribution pattern of vegetation, and landscape perimeter riparian ecosystem of Mount Merapi. The results showed the most vegetation indeks is Falcataria moluccana is 58,03 and ecosystem has 18 of specific vegetation with eac indeks value. Identification of riparian ecosystem landscape models currently on ecological density range called Ecological Density occupying to 300 m/Ha. While the actual SDI conditions based on ground check has a mean value of 2.52. Analys riparian model based of ecological functions and economic values obtained optimum value the riparian model thatt have agroforestry land cover are dispersi and ‘tegalan’ as agroforestry practices by human activity. Keywords : Riparian, Agroforestry, Silviculture, Landscape